Development of Vocal Teaching Materials Based on Keroncong Singing Or- naments to Strengthen Western Vocal Technique - Diah Latifah; Rita Milyartini (LP2M ISBI Bandung, 2017)
ABSTRACTThis study develops teaching materials based on “Luk Keroncong Song Ornaments